2017
DOI: 10.2147/dddt.s126743
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits transforming growth factor-β2-induced epithelial-to-mesenchymal transition in human retinal pigment epithelial cells by suppressing the Smad pathway

Abstract: Proliferative vitreoretinopathy (PVR) is the main cause of failure following retinal detachment surgery. Transforming growth factor (TGF)-β2-induced epithelial-to-mesenchymal transition (EMT) plays an important role in the development of PVR, and EMT inhibition decreases collagen gel contraction and fibrotic membrane formation, resulting in prevention of PVR. Resveratrol is naturally found in red wine and has inhibitory effects on EMT. Resveratrol is widely used in cardioprotection, neuroprotection, chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Evidence has shown that RSV suppresses cancer metastasis through inhibiting TGFβ induced EMT . To further delineate the role for TRPM7 in modulating RSV‐mediated inhibition of EMT, we assessed migration of DU145 and PC3 cells with and without TGFβ treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that RSV suppresses cancer metastasis through inhibiting TGFβ induced EMT . To further delineate the role for TRPM7 in modulating RSV‐mediated inhibition of EMT, we assessed migration of DU145 and PC3 cells with and without TGFβ treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Poricoic acid G and poricoic acid H suppressed TGF-β/Smad pathway by selectively inhibiting the phosphorylation of Smad3 via blocking the interactions of SARA with TGFβRI and Smad3 [178]. Similarly, renal fibrosis in a variety of animal models were attenuated or suppressed through TGF-β/Smads and NF-κB-mediated pathways by administration of compounds isolated from various natural products, such as GQ5 [179], arctigenin [98], curcumin [180,181], resveratrol [182], berberine [183,184], sinomenine [185], rutin [186], oxymatrine [149,187], bergenin [188], oleanolic acid [189], tanshinone IIA [190], leonurine [191]; (+/−)-sinensilactam A [192], epigallocatechin-3-gallate [193] and astragaloside IV [194,195].…”
Section: Specific Inhibition Of Smads Signaling By Natural Productsmentioning
confidence: 99%
“…Previous work also has indicated that RESV can affect migration of various cancer cells, 24,25 and it has been suggested that RESV may inhibit migration of ARPE-19 retinal epithelial cells. 26 RESV treatment resulted in a significant reduction in transdifferentiation from lens epithelial cells to myofibroblasts. The profibrotic cytokine, TGFb is heavily involved in the development of PCO and EMT in particular.…”
Section: Discussionmentioning
confidence: 92%